Functional and structural changes of the human proximal small intestine after cytotoxic therapy. Issue 3 (March 1985) - Cunningham, D; Morgan, R J; Mills, P R; Nelson, L M; Toner, P G; Soukop, M; McArdle, C S; Russell, R I
Abstract : The effects of cytotoxic therapy on the structure and function of the proximal jejunum were studied in six patients receiving intravenous cyclophosphamide (300 mg/m2), methotrexate (40 mg/m2), and 5-fluorouracil (600 mg/m2) as adjuvant therapy for breast cancer. Using a steady state, triple lumen tube perfusion system the absorption of water and electrolytes was measured before and 48 h after administration of the cytotoxic agents. Jejunal biopsies were obtained at each perfusion. Median (range) water absorption fell from 126 (40-142) to 84 (46-142) ml/h/30 cm, with parallel changes for electrolytes; none of the changes was significant. Brush border disaccharidases did not change at 48 h after chemotherapy, while mature enterocytes appeared normal by both light and electron microscopy. Crypt cells and immature enterocytes, however, showed focal vacuolation by light microscopy, corresponding to the occurrence of large residual bodies (secondary lysosomes) containing partially degraded fragments of damaged crypt cells. The confinement of ultrastructural changes to the immature cell population may explain the failure of this study to show a consistent change in the absorptive function of the jejunum 48 h after chemotherapy.